José Raúl Capablanca : a chess biography - Sánchez, Miguel Á., 1947- (McFarland & Company, Inc., Publishers, 2015)
"Meticulously researched, utilizing many sources available only in Capablanca's home country, it puts truth to legend regarding a man who stood astride the chess world in of its most dynamic and dramatic eras. Numerous games and diagrams complement the text, as do a wealth of photographs"--